(untitled) (e-Journal of Linguistics, 2020)
The study deals with the types of maxim violation in Indonesian Lawak Klub (ILK) done by the main speakers. The objectives of study were to describe the violation of maxim, to describe the dominant type of maxim violating and the reason of violating maxim. The data were the dialogue of main speakers in Indonesian Lawak Club (ILK). This research was conducted using descriptive qualitative and focused on one episode of cara cepat menjadi kaya. The findings showed that there are 70 violating of maxim of quantity, 71 violating of maxim of quality, 144 vioalating of maxim of relevance, and 27 violating of maxim of manner. The reasons of the dominant violating of maxim of relevance are to widen discussion related to the topic and make interactive and atractive discussion.